Antibacterial Effects of Quinazolin-4(3H)-One Functionalized-Conjugated Silver Nanoparticles - Abdulkader Masri; Ayaz Anwar; Naveed Ahmed Khan; Muhammad Saquib Shahbaz; Khalid Mohammed Khan; Syed Shahabuddin; Ruqaiyyah Siddiqui (MDPI AG, 2019)
Infections due to multi-drug resistant bacteria are on the rise and there is an urgent need to develop new antibacterials. In this regard, a series of six functionally diverse new quinazolinone compounds were synthesized by a facile one-pot reaction of benzoic acid derivatives, trimethoxymethane and aniline derivatives. Three compounds of 3-aryl-8-methylquinazolin-4(3H)-one, and 3-aryl-6,7-dimethoxyquinazolin4(3H)-one were prepared and tested against multi-drug resistant bacteria. Furthermore, we determined whether conjugation with silver nanoparticles improved the antibacterial efficacy of these quinazolinone derivatives. The newly synthesized compounds were characterized by ultraviolet visible spectrophotometry (UV-vis), Zetasizer analysis, Fourier transform infrared spectroscopic methods (FT-IR), and scanning electron microscopy (SEM). Using bactericidal evaluation, effects were determined against selected Gram-negative and Gram-positive bacteria. Furthermore, cytotoxicity of nanoconjugates on human cells were determined. The UV-vis spectrum of silver nanoparticles conjugated quinazolinone displayed surface plasmon resonance band in the range of 400−470 nm, and the size of nanoparticles was detected to be in the range of 100−250 nm by dynamic light scattering (DLS). FT-IR study confirmed the stabilization of silver nanoparticles by the presence of diverse functional arayl on each compound. SEM further revealed the construction of spherical nanoparticles. Among the quinazolinone derivative tested, two compounds (QNZ 4, QNZ 6) conjugated with silver nanoparticles showed enhanced antibacterial activity against Escherichia coli K1, Streptococcus pyogenes, Klebsiella pneumoniae, B. cereus and P. aeruginosa as compared to the compounds.